Oral Health Impact Profile (OHIP-14) and its association with dental treatment needs of adolescents in a rural Nigerian community (2016)
To validate and determine the applicability of OHIP-14 in assessing the impact of unmet dental treatment needs on the quality of life of adolescents in a rural community. Methods: The OHIP-14 questionnaire and the Aesthetic component (AC) of Index of Orthodontic Treatment Need (IOTN) were data collection instruments in a cross sectional survey among students in a rural community. The reliability and validity of the OHIP-14 as well as the association between it and dental treatment needs including malocclusion was assessed. Data obtained was analyzed using Mann Whitney U Test. Results: The mean age of participants was 14.9 (±1.6) years. The OHIP-14 had acceptable Cronbach alpha value of 0.8. It could discriminate between respondents with or without dental treatment needs due to caries and dental trauma (p <0.001). The OHIP-14 did not differentiate between respondents with or without orthodontic treatment need (p= 0.808). However, significant association existed between being irritable with people and unmet orthodontic treatment needs (p= 0.032). Conclusion: The OHIP-14 is a valid and reliable quality of life assessment tool in young adolescents in this rural community. However, only the social disability domain component discriminated significantly between those with or without orthodontic treatment needs